The physico-chemical Properties of Beef Meatballs processed by Addition of Different Salt Concentration Using the Ohmic Heating method - Aprisal Nur Aprisal; Hikmah M Ali; Salengke Salengke (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2021)
Meatballs are generally cooked using the conventional method, namely the conduction method or using a stove, this cooking has several drawbacks including the amount of energy wasted during cooking, a long time and an uneven level of maturity. Currently, many ohmic cooking technologies have been developed as a substitute for conventional cooking. This technology has advantages such as being environmentally friendly because it does not use fossil fuels and the temperature is easily controlled. This technology uses the principle of electrical resistance (ohms) to generate heat, so that the heat that arises comes directly from the product itself, not from heat that is outside, such as fire or radiation. The main requirement that must be met is that the material must have conductivity or be able to conduct electric current. Salt is one of the electrolytes that are able to conduct electric current so that ohmic technology can be applied to meatballs. This study aims to determine the effect of salt concentration on the physico-chemical characteristics of beef meatballs. Three levels of salt concentration (2%, 3%, and 4%) tested on 9 samples of meatballs. The results showed an increase in the strength of Gel (P<0.01), antioxidant activity (P<0.05) and dissolved protein content (P<0.01) with increasing salt concentration given. This study concluded that the use of ohmic technology gave good characteristics of meatballs where this cooking was able to increase gel strength, antioxidant activity and protein content. Keywords : Ohmic heating, meatball, salt, cooking time, beef